Navigating the Political Terrain: How Political Contestation among National Sufi Ulama shaping Political Preferences of Muslim Society in Indonesia - Santoso, Try Riduwan; Abdullah, Irwan; Basuki, Nanda Ahmad; Yusuf, Muhammad; Sari Rahayu, Solihah (UIN Sunan Kalijaga Yogyakarta, 2023)
The involvement of Sufi Ulama of Tarekat Qadariyah-Naqsabandiyah (TQN) Jagaraya in political contestation provides a distinct approach to introduce the presidential candidates they supported in the 2019 Indonesian presidential election. In contrast to the conventional guru-disciple attachment, the Sufi ulama adopt various strategies to modify the standpoint of their Tarekat member and align it with particular political tendencies. The intent of this study is to identify the strategies implemented by the Sufi ulama to collect support for their preferred political candidates within the Tarekat community. By utilizing a qualitative methodology, this study revealed various strategies used by those ulama in introducing political leaders, yet additionally taking the congregation's view regarding its process into consideration. Kiai Raga, with his traditional religious intellectual background, adopts traditional methods of gathering tarekat members who are interested in traditional tarekat rituals. Kiai Alam, on the other hand, embraces digital media to promote his political stance. These two varied methods by the two nationals Sufi Ulama display a dynamic combination of invention and adaptation, reflecting their diverse efforts to accommodate the political preferences of their respective tarekat members.